2009
DOI: 10.1007/s11294-009-9206-y
|View full text |Cite
|
Sign up to set email alerts
|

Some Empirical Evidence of the Efficacy of Job Matching in Urban Labor Markets

Abstract: Job search, Job matching, Urban labor markets, Coordination hypothesis, J0, J62, R0, R23,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…This is in contrast to studies linking urbanity to positive chances (Yankow, 2009) and in line with our reasoning that low-educated workers suffer from more competition. However, this effect is significant at only the 10% level when a nonnative measure is used.…”
Section: Labor Market Characteristicssupporting
confidence: 79%
See 1 more Smart Citation
“…This is in contrast to studies linking urbanity to positive chances (Yankow, 2009) and in line with our reasoning that low-educated workers suffer from more competition. However, this effect is significant at only the 10% level when a nonnative measure is used.…”
Section: Labor Market Characteristicssupporting
confidence: 79%
“…Low-educated workers can benefit from a higher abundance o f better jobs and consumption effects. (H ensen et al, 2009;Yankow, 2009). However, w ith respect to the low educated, w e m ight question w hether they are also better o ff in urban areas, since m ore com petition m ay be experienced when the higher educated are attracted to the bigger cities and take the best jobs.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…On one hand, job search is more likely to pay off in urban areas, as there are more developed labor markets in which it is more likely that there are a lot of good high return jobs that are worth searching for. On the other hand, costs of search are lower in urban labor markets due to the high density of employers and lower transportation costs [13], [23]- [24].…”
Section: B Household Characteristicsmentioning
confidence: 99%
“…Unemployed people, in their prime work age, males or females, are expected to be most active in job search [13]. However, it is worth mentioning that the odds of doing a job search for females (30)(31)(32)(33)(34)(35)(36)(37)(38)(39) are ceteris paribus 3.6 times as likely as for females (40+), while the odds of doing a job search for female unemployed youth (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) are ceteris paribus 2.1 times as likely as for females (40+). Young females are less active than females (30)(31)(32)(33)(34)(35)(36)(37)(38)(39).…”
Section: B Determinants Of Women's Job Search Propensitymentioning
confidence: 99%
“…These empirical studies have found that larger and thicker urban labor markets enhance worker productivity by allowing for a greater specialization of professional activities (Baumgardner, 1988;Garicano and Hubbard, 2007); helping to solve dual-career problems (Costa and Kahn, 2000); facilitating more assortative matching between workers and firms (Andersson, Burgess, and Lane, 2007); improving the efficiency of job search (Yankow, 2009;Di Addario, 2011), and reducing labor market churn (Wheeler, 2008;Bleakley and Lin, 2012). While this work has improved our understanding of the benefits of urban agglomeration, the empirical evidence surrounding job matching as a source of urban agglomeration economies remains, so far, largely indirect in nature.…”
Section: Introductionmentioning
confidence: 99%